Optimal fiscal and monetary policy under imperfect competition - Stephanie Schmitt-Grohé; Martín Uribe (Rutgers University, Department of Economics, 2001)
This paper studies optimal fiscal and monetary policy
Keywords: E61; E63; 330; Friedman rule; Imperfect competition; Optimal taxation; Geldpolitik; Geldmengensteuerung; Finanzpolitik; Unvollkommener Wettbewerb; Theorie